ASPECTOS ÉTICOS Y DEONTOLÓGICOS DE LA COBERTURA PERIODÍSTICA DE LAS CATÁSTROFES TECNOLÓGICAS: EL CASO DEL ACCIDENTE FERROVIARIO DE SANTIAGO DE COMPOSTELA (2013) - Lda. Alba ALMENARA (Fonseca, Journal of Communication, 2023)
This study examines the ethical-deontological aspects in media coverage of technological disasters, taking as case subject the most important railway accident in Spain of the last 40 years, which took place on the 24 of July 2013 in Santiago de Compostela. To do so, in first place, it presents a systematic review of Spanish self-regulation of journalistic documents related to the coverage of accidents, disasters, in particular technological disasters.